No Consistent Link Between Dust Storms and Valley Fever (Coccidioidomycosis). (29th November 2021) - Comrie, Andrew C.
Abstract: Dust storms, such as those associated with haboobs and strong regional winds, are frequently assumed to cause increases in cases of Valley fever (coccidioidomycosis). The disease is caused by inhaling arthroconidia of Coccidioides fungi that, after being disturbed from semi‐desert subsoil, have become airborne. Fungal arthroconidia can be transported in low‐wind conditions as well as in individual dust events, but there is no reliable evidence that all or most dust storms consistently lead to subsequent increases in coccidioidomycosis cases. Following a review of the relevant literature, this study examines the relationship between dust storms and coccidioidomycosis cases to determine if there is a consistent and general association between them. All recorded dust storms from 2006 to 2020 in and near the Phoenix area of Maricopa County, Arizona and the Bakersfield area of Kern County, California were used in a compositing analysis (superposed epoch analysis) of subsequent coccidioidomycosis cases in each area. Analyses of monthly and weekly disease case data showed no statistical differences in the patterns of coccidioidomycosis cases following dust storms versus non‐dust storm conditions, for the entire data set as well as for seasonal subsets of the data. This study thoroughly analyzes post‐dust storm coccidioidomycosis cases for a large set of dust storms, and it confirms and expands upon previous literature, including a recent study that measured airborne arthroconidia and found no consistent links connecting wind and dust conditions to increases in coccidioidomycosis. Plain Language Summary: Valley fever affects thousands of people annually in Arizona and the southern San Joaquin Valley of California, as well as parts of Central and South America. It is caused by inhaling microscopic spores of a soil fungus that become airborne when affected soil is disturbed. Because disturbances such as digging can create dust clouds, it is intuitive to assume that large dust storms like haboobs will increase the risk and cases of the disease. Indeed, this connection is commonly made in the scientific literature and in popular media. However, there is limited evidence of individual dust storms being followed by increases in Valley fever cases, and there is no indication that dust storms consistently lead to more cases. This study thoroughly analyzes Valley fever cases following dust storms over many years. It found no statistical differences between Valley fever occurrence after dust storms and after non‐dust storm conditions. This finding is consistent with a recent innovative spore measurement study. An implication is that, while dust storms are dangerous for other reasons, we need to avoid always linking them to Valley fever, and instead emphasize established risks associated with disturbance of affected soil. Key Points: It is often asserted that large dust storms like haboobs generally lead to increases in cases of Valley fever (coccidioidomycosis) This study thoroughly tests that assertion using dust storm and coccidioidomycosis case data over many years Consistent with literature, results show no statistical difference in cases of the disease after dust storm and non‐dust‐storm conditions